2017
DOI: 10.1093/humrep/dex090
|View full text |Cite
|
Sign up to set email alerts
|

The ovarian response in fragile X patients and premutation carriers undergoing IVF–PGD: reappraisal

Abstract: None.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…A review of published research on the FMR1 gene and its effect on IVF outcomes yielded 16 articles (Gleicher et al, 2009;2012a;2012b;2013a;2013b;Bibi et al, 2010;Tsafrir et al, 2010;Lledo et al, 2012;Weghofer et al, 2012;Elizur et al, 2014;Kushnir et al, 2014;Banks et al, 2016;Morin et al, 2016;Avraham et al, 2017). Nine of those were from the same research group (Gleicher et al, 2009;2012a;2012b;2013a;2013b;Weghofer et al, 2012;Kushnir et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A review of published research on the FMR1 gene and its effect on IVF outcomes yielded 16 articles (Gleicher et al, 2009;2012a;2012b;2013a;2013b;Bibi et al, 2010;Tsafrir et al, 2010;Lledo et al, 2012;Weghofer et al, 2012;Elizur et al, 2014;Kushnir et al, 2014;Banks et al, 2016;Morin et al, 2016;Avraham et al, 2017). Nine of those were from the same research group (Gleicher et al, 2009;2012a;2012b;2013a;2013b;Weghofer et al, 2012;Kushnir et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…In three out of four studies, it was suggested that premutation carriers may have reduced success (oocyte yield, pregnancy rate and live birth rate) with IVF treatment compared with women with either a normal CGG repeat or a full mutation (Bibi et al, 2010;Tsafrir et al, 2010;Elizur et al, 2014), with the largest study (n = 51 premutations) finding no relationship between the specific repeat length and the oocyte yield (Avraham et al, 2017). Future studies that provide additional data will be beneficial in helping counsel patients with premutations before moving forward with ovarian stimulation for IVF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is thought to occur via overproduction of abnormal FMR1 mRNA, which may lead to either a reduced NGF pool and/or abnormally rapid depletion of oocytes (16). There also have been several studies regarding abnormal CGG repeat number and DOR (16,26,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39). In studies by Welt et al (32) and Hundscheid et al (33), regularly cycling premutation carriers were found to have increased FSH levels compared with age-matched controls.…”
Section: Fragile X Mental Retardation Genesmentioning
confidence: 99%
“…While some authors considered PGT-M for FRAX patients as an "unrealistic option" due to its inefficiency [10], various PGT centers nowadays offer this strategy for FRAX mutation or premutation carriers and several reports have been published with contradictory results. On the one hand, Platteau and colleagues as well as Avraham and his team showed that premutation carriers required a higher dose of FSH for ovarian stimulation and were at higher risk of cancellation for low ovarian response [20,21]; on the other hand, Tsafrir and colleagues reported that premutation carriers necessitated less FSH and had more retrieved oocytes than mutation carriers [22]. Moreover, some studies suggested that the number of CGG repeats is correlated with ovarian response [23] and that the lowest response is observed in women with mid-size CGG repeats (80-120) [24].…”
Section: Introductionmentioning
confidence: 99%